The 291-nm band system of 3-fluorostyrene: ground state vibrational assignments for the cis and trans rotamers from their supersonic jet spectra - Hollas, J. Michael; Hussein, Mohd Zobir (Elsevier, 1989)
Single vibronic level fluorescence spectra, with excitation in the O& 4 1;42& 42& and 29h bands of cis 3-fluorostyrene and in the 08 band of trans 3-fluorostyrene, have been obtained in a super-sonic jet. Assignments of these spectra show that some vibrational fundamentals, particularly those involving the part of the molecule in the region of the vinyl group, are appreciably different in the two rotamers. In the So electronic state the cis rotamer is 220 cm-’ lower in energy than the tram and this difference is increased to 495 cm-’ in S, . The cis-trans barrier is increased from 1150 cm-’ in S, to about 2500 cm-’ in S, but a strong Duschinsky effect, affecting the C(1)-C(cx) torsional vibration, makes the barrier in s, very uncertain.